Estudio de implementación de paneles solares para la captación de energía solar en el suministro de energía para un cargadero de carrotanques en la transferencia de hidrocarburos. (2022)
In the present work, the feasibility analysis of installing solar panels for the supply of energy for the equipment of a tank car loading system was carried out. To carry out this feasibility analysis, it was first necessary to determine in which sector of Colombia the highest solar radiation occurs. Subsequently, the electrical power required by the equipment is determined and in this way define the number of solar panels, this allows us to know the technical feasibility. To finalize the project, the respective financial analysis will be carried out where all the costs of a tank car loading system without using solar panels and using that renewable energy are taken into account to compare the values ​​and be able to conclude its viability.